The Influence of Leadership Style on Organizational Commitment with Job Satisfaction as a Mediating Variable at PT XYZ - Fransiska Aprodite Afianto; R. Iqbal Robbie; Sandra Irawati (Universitas muhammadiyah malang, 2025)
The purpose of this study is to determine the effect of leadership style on organizational commitment with job satisfaction as a mediating variable. This research was conducted on employees of PT XYZ using the proportional random sampling method, with a total sample of 96 respondents. This study employs a quantitative approach with path analysis using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) through the SmartPLS version 4.1.1.2 application. The results of this study indicate that leadership style does not have a significant effect on organizational commitment, job satisfaction does not have a significant effect on organizational commitment, there is a significant relationship between leadership style and job satisfaction, and job satisfaction does not successfully mediate the relationship between leadership style and organizational commitment. Further research is needed to identify other factors that influence organizational commitment in the company.